Valuation and aspirations for drip irrigation in Punjab, Pakistan - Bell, Andrew R.; Ward, Patrick S.; Ashfaq, Muhammad; Davies, Stephen (American Society of Civil Engineers, 2020)
Modern drip-irrigation technologies improve water-use efficiency while simultaneously transforming areas that are not otherwise irrigable in practice (too distant or too high to be reached by surface waters). Although drip irrigation is expanding rapidly in India, adoption remains low in neighboring Pakistan. To gain deeper insight into the factors constraining adoption of drip irrigation in Pakistan, a discrete choice experiment framed around the hypothetical subsidized purchase of a drip-irrigation system in four districts within Pakistan’s Punjab Province was used. The results show higher valuation of drip systems among new users, which suggests that limited technical support and upstream maintenance facilities are not posing significant barriers to drip-irrigation adoption. It was observed that aspirations for cropping systems under drip were better predictors of farmers’ valuation for drip systems than current cropping patterns, implying that a different agricultural landscape might reasonably emerge under more widespread adoption of drip. Both aspirations were observed for high-value crops such as fruits, as well as lower-value crops such as wheat, under drip systems, suggesting a number of ways through which drip irrigation may transform Pakistan’s agricultural landscape.